Validation of Employers Views on Soft and Hard Job Skills of Nigeria Polytechnic Construction Graduates - Nor Fadila Amin; Shirka Kassam Jwasshaka; Adibah Abdul Latif (Universitas PGRI Semarang, 2020)
In a perfectly competitive labour market, the demand for skills is the duty of employers to supply the necessary skills. Knowledge and abilities of graduate competencies should represent the needs of the industry. Such qualities include both academic and generic skills in their chosen professions needed for work. To prepare completely for the unpredicted and ever-changing nature of the workplace, graduates need a range of skills specific to labour-employers. The aim of this pilot study is to identify whether the polytechnic building graduates have the right job skills from the perspective of employers. The cross-sectional survey was adopted to select 60 experts who responded to 169 items questionnaire, purposeful sampling technique was used. The items comprised of components of both hard and soft job skills. Inferential statistics and Rasch measurement model were used to analyse construct reliability and to determine fit statistics, point measurement correlation and standard residual. The result showed that the validity of the instrument's contents values was almost perfectly accepted. In addition, employers were unanimous in their views on the essentials of hard and soft skills in establishing a competency framework. The feasibility study will have a huge impact on researchers as it will direct them in carrying out the main analysis relating to the development of competences for employment.